FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI KABUPATEN GORONTALO PERIODE 2017-2021 - Harijono Imbran (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2023)
This study aims to determine the factors that influence the economic growth of Gorontalo Regency for the 2017-2021 period. This study uses a descriptive quantitative research approach. The data source used is secondary data for 2017-2021, namely data on economic growth, population growth, population age groups and workforce development. The analytical tool used is multiple linear.The results of the study show that population growth has a significant effect on economic growth in Gorontalo Regency for the 2017-2021 period. The dependency ratio has a significant effect on economic growth in Gorontalo Regency for the 2017-2021 period partially. The total workforce has a significant effect on economic growth in Gorontalo Regency for the 2017-2021 period partially